Estudo da influência dos parâmetros operacionais de células a combustível do tipo PEM utilizando geometria dos canais de distribuição dos gases diferentes no eletrodo catódico - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
A fuel cell is a device that converts chemical energy into electrical energy continuously and directly . In the PEMFC system, reagents are typically provided humidified but the excess water can be condensed and thereby reduce the cell performance because it prevents diffusion of the gas. This problem is most critical at the cathode, because besides this condensation occurs the formation of water as a product of the electrochemical reaction. The produced water must be removed from the cathode by removing it through the gas diffusion layer to the flow fields and then out of the cell. In this work, a comparative study of different flow fields cathode using plates for gas distribution models, interdigital and trapezoidal. We evaluated the performance of the fuel cell plates by comparison with the conventional model of gas distribution, serpentine. Whereas the flooding of the electrode is one of the main limiting current was also carried out to compare the performance of these plates for different compositions of cathode diffusion layer, changing the amount of PTFE incorporated in addition to the temperature and pressure of the reactant gases. It was observed that the temperature of dampers different cell provides an increase in efficiency due to increase of water present in cell. The models had a similar optimum temperature of operation, the trapezoidal model excels at medium currents due to better efficiency in the removal of water present in the cathode. Increased pressure favors the entire polarization curve, however the combined effects of temperature x pressure is more pronounced in the model trapezoidal. Containing 30% polytetrafluoroethylene present in the gas diffusion layer showed better results in most of the analyzed temperatures
Keywords: Fonte energética; Combustíveis; Células a combustível; Eletrodos de Difusão de Gás - EDG; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA